PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR DPR RI KOMISI X: PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Rifky, Rifky Hermiansyah; Sondjaya, Trisna (NIAGARA Scientific Journal, 2024)
The House of Representatives of the Republic of Indonesia (DPR RI) has the responsibility of managing employment, health, and social welfare. Related to the work performance of employees at the DPR RI Commission X office in Jakarta, observations indicate a decline attributed to several factors, particularly in transformational leadership, where the leadership is assessed as still lacking in inspiring other employees towards achieving goals. The approach in this research is quantitative. According to Sugiyono (2020:16), quantitative research methods can be defined as research methods based on positivist philosophy, used to study a specific population or sample, data collection using research instruments, data analysis being quantitative/statistical, with the aim of testing established hypotheses. The testing of construct validity through factor analysis of research instruments is intended to measure the influence of Transformational Leadership and Organizational Culture on the Performance of Employees of Commission X of the Indonesian House of Representatives (DPR RI). The variable used in this study is Transformational Leadership. The total score, which is the sum of all item scores, is calculated using the Product Moment correlation formula with an alpha of 5%. The results of the study indicate that Transformational Leadership in Commission X of the DPR RI, based on calculations with SPSS, shows a relationship between Transformational Leadership and Employee Performance of 0.146. The correlation of Organizational Culture with Employee Performance, based on SPSS calculations, yields a correlation value of 0.332. Entrepreneurial Interest Based on the results of data processing from research with the assistance of SPSS 27.0.1 calculations.